Assessment of N-acetylcysteine as a therapy for phosgene-induced acute lung injury. (15th June 2018) - Rendell, Rachel; Fairhall, Sarah; Graham, Stuart; Rutter, Steve; Auton, Philippa; Smith, Adam; Perrott, Rosi; Jugg, Bronwen
Highlights: Inhalation of phosgene can cause an acute lung injury via complex mechanisms. Oxidative stress is believed to play a fundamental role in phosgene-induced lung injury. NAC has anti-oxidant, mucolytic and anti-inflammatory activity which may be beneficial in treating phosgene lung injury. Multiple nebulisations of NAC were ineffective against phosgene-induced acute lung injury. There remains no specific, evidence based pharmacological treatment for phosgene-induced lung injury. Abstract: The toxic industrial chemical (TIC 1 ) phosgene remains an important chemical intermediate in many industrial processes. Inhalation of phosgene can cause an acute lung injury (ALI) which, in severe cases may result in death. There are currently no effective pharmacological therapies or evidence-based treatment guidelines for managing exposed individuals. N -acetylcysteine (NAC) is a commercially available drug licensed in the UK and elsewhere for the treatment of paracetamol (acetaminophen) overdose. It has a number of mechanisms of action which may provide therapeutic benefit for the treatment of phosgene-induced ALI. It has previously been shown to provide therapeutic efficacy against the lung damaging effects of sulfur mustard vapour exposure, when given by the inhaled route, in the pig (Jugg et al., 2013). Our research objective was to determine whether inhaled NAC might also be therapeutic for other chemicals, in this case, phosgene. This study has demonstrated that multiple nebulised doses, administered from 30 min after exposure of terminally anaesthetised pigs to phosgene, is not an effective therapy when administered at the times and doses employed in this study. There remains no pharmacological treatment for phosgene-induced lung injury.